Intrauterine insemination in women older than 38 years, is it worth while? - Manzur, Alejandro (2014)
Objectives: To determine cost-effectiveness in homologous intrauterine insemination (IUI) outcomes in women 38 years or older in a human reproduction unit and compare results with those of women of similar age treated with complex assisted reproduction technology as published by the Latin American Assisted Reproductive Registry (RedLara) 2009. Design: Retrospective, comparative study. Setting: Unidad de Reproduccion Humana, Pontificia Universidad Catolica de Chile, Santiago, Chile. Participants: Women treated with homologous intrauterine insemination. Interventions: Review of results obtained in 5 421 homologous intrauterine insemina tion cycles (IUI) performed between January 2000 and September 2011. In order to analyze the impact of advanced maternal age, we compared rates obtained in women younger than 38 years old (4 000 cycles) with those of women 38 years and older (1 421 cycles). We describe clinical pregnancy rates with the different ovarian stimulation protocols. Cost-efficiency analysis with three IUI cycles before opting for in vitro fertilization (IVF) in women older than 38 years instead of directly doing IVF was compared with performance of IVF/ICSI cycles with own oocytes in women 38 years and older obtained from the Latin American Assisted Reproductive Registry (RedLara) 2009. Main outcome measures: Cost-efficiency analysis when trying three IUI cycles before opting for IVF in women older than 38 years. Results: A total of 600 clinical pregnancies were included in the series, with 11.1% clinical pregnancies rate per IUI cycle and 5.3% multiple pregnancy rate. In women 38 years and older, there was a significant decline in those rates (7.5% and 2.8%, respectively). Clinical pregnancy rates with different ovarian stimulation protocols showed benefit of gonadotropin schemes. Cost-effective analysis demonstrated benefit in prescribing three IUI cycles when inclusion criteria were met before going through IVF, compared to performing IVF from the start. Conclusions: Both clinical pregnancy and multiple pregnancy rates declined in women 38 year-old or more. Cost-efficiency analysis showed benefit in trying three IUI cycles in women satisfying inclusion criteria before opting for in vitro fertilization (IVF) instead of performing IVF from the start.